Circular RNA PVT1 Promotes Breast Cancer Progression via miR-30b-5p/AEG-1 Axis - Yingdong Li; Wenfang Li; Yongbiao Ai; Tianxiang Zhang (IMR Press, 2024)
Background: Circular RNA PVT1 (circPVT1) is involved in malignant tumorigenesis. However, the function of circPVT1 in breast cancer (BC) has not been investigated. The purpose of this research is to explore the mechanisms of circPVT1 in breast cancer from different perspectives. Methods: In this study, the expressions of circPVT1 and microRNA-30b-5p (miR-30b-5p) were analyzed by quantitative real-time polymerase chain reaction (q-PCR). The Kaplan-Meier was adopted to compare disease free survival (DFS) and overall survival (OS). CircPVT1 was depleted with special si-RNA, Cell Counting Kit-8 (CCK-8) to evaluate the cell viability and transwell assays to examine invasion ability. Astrocyte elevated gene 1 (AEG-1) protein level was measured by western blot. The competitive endogenous functions among circPVT1, miR-30b-5p and AEG-1 were verified by bioinformatics analysis and luciferase assay. Results: In this study, it was found that the circPVT1 was significantly elevated in BC tissues and cell lines compared to the control group. The Kaplan-Meier results indicated that higher circPVT1 expression had a worse prognosis than the low circPVT1 expression group in DFS (χ2 = 7.174, p = 0.007) and OS (χ2 = 3.946, p = 0.047). CircPVT1 regulated the BC cell viability, migration, and invasion ability. Besides, miR-30b-5p was found as a molecular target of circPVT1, and AEG-1 was identified as a target of miR-30b-5p. The suppression of circPVT1 promoted the expression of miR-30b-5p and inhibited AEG-1 expression. Moreover, simultaneous inhibition of miR-30b-5p expression in the circPVT1 knockout group could reverse the inhibition of AEG-1. Conclusions: Our results indicate circPVT1 regulates AEG-1 expression by binding to miR-30b-5p in breast cancer cells. CircPVT1 promoted AEG-1 expression by inhibiting miR-30b-5p in order to enhance the BC cell viability, migration, and invasion. Our results reveal a new molecular therapy target for breast cancer.